The Role of Internal and External Audit Committees in Reducing Banking Failure - Mohsin , Hayder Jerri (South Asian Journal of Social Sciences and Humanities, 2023)
Purpose: This study seeks to identify the role of internal and external audit committees and their impact on limiting bank failure. Research Design: The research included a quantitative analysis of data on commercial banks in the south of the country under study, which numbered (6) commercial banks. The study sample included a group of (77) employees working in these banks The analysis is based on a solid base that sought to reveal the practices of these banks in the role of internal and external audit committees and their impact on reducing bank failure. The study sought to test the effect and correlation relationship between the independent variable represented by the internal and external audit committees and the variable affiliated with the bank, failure and deportation. Data were processed by statistical methods using (SPSS) program. Results: The results of the statistical analysis of the data collected through the questionnaire tool prepared for this purpose showed that there is an effect and correlation between the independent variable of the internal and external audit committees and the variable dependent on bank failure and its dimensions (information asymmetry, credit risk, systemic risk, moral dimension).